Health, medicine, and the sea : Australian voyages, c.1815-1860 - Foxhall, Katherine (Manchester University Press ; Distributed in the U.S. by Palgrave Macmillan, 2012)
During the 19th century, over 1.5 million migrants set sail from the British Isles to begin new lives in the Australian colonies. Health, medicine and the sea follows these people on a fascinating journey around half the globe to give a rich account of the creation of lay and professional medical knowledge in an ever-changing maritime environment.